THE SPATIAL ORGANIZATION MORPHOLOGY AND THE VARIABILITY OF THE CEREBRAL DURA MATER SINUS DRAINAGE OF CANIS LUPUS FAMILIARIS - Cherno, V.S.; Vovk, Yu.M. (World of Medicine and Biology, 2012)
The spatial organization and the intraspecies variability of the sinus drainage forms were investigated on the corrosion preparations of the sinuses of the cerebral dura mater in the domestic dog, Canis lupus familiaris. Morphological trends of the superior sinus drainage through division and anastomoses formation were identified. Shapes and forms of the anastomoses between sinus components were idintified and characterized.
Keywords: sinus drainage; form variability; Canis lupus familiaris